Correlation Between Pain, Disease Activity, and Rheumatoid Factor Positivity in Patients with Chikungunya Arthritis - Amaral, José Kennedy; Schoen, Robert Taylor; Bingham, Clifton O.; Firmino, Paulo Renato Alves; Cândido, Estelita Lima (The Yale journal of biology & medicine, 2024)
Chikungunya fever (CHIKF) is an acute viral disease caused by the chikungunya virus (CHIKV) transmitted by mosquitoes. The acute phase presents with limited symptoms and low mortality, but approximately half of cases progress to more chronic illness with persistent and disabling joint symptoms. To better characterize the burden of chronic disease, we analyzed the relationship between pain intensity, the Disease Activity Index by DAS28-ESR, rheumatoid factor (RF) positivity, sex, and age in a retrospective cohort of 133 patients with chikungunya arthritis (CHIKA). We assessed all subjects by clinical evaluations, and laboratory testing, including the Pain Visual Analog Scale (VAS), the Disease Activity Score (DAS28-ESR), and RF measurement. We observed that pain intensity increased significantly with disease activity (ρ = 0.416 and p-value < 0.05) and with age (ρ = 0.259 and p-value = 0.003). Despite a predominance of women in our cohort, sex/gender was not associated with increased pain risk. Our study demonstrated a strong correlation between pain and disease activity, but assessment of these variables in a larger, prospective cohort should be undertaken to further characterize risk variables and improve therapy for patients with CHIKA.